2015
DOI: 10.1016/j.devcel.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

SCML2 Establishes the Male Germline Epigenome through Regulation of Histone H2A Ubiquitination

Abstract: SUMMARY Gametogenesis is dependent on the expression of germline-specific genes. However, it remains unknown how the germline epigenome is distinctly established from that of somatic lineages. Here we show that genes commonly expressed in somatic lineages and spermatogenesis-progenitor cells undergo repression in a genome-wide manner in late stages of the male germline and identify underlying mechanisms. SCML2, a germline-specific subunit of a Polycomb repressive complex 1 (PRC1), establishes the unique epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
217
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(236 citation statements)
references
References 66 publications
(87 reference statements)
16
217
1
2
Order By: Relevance
“…Another proteomics study independently identified SCML2 as a meiosis-specific protein (Luo, et al 2013). Scml2 is highly transcribed in spermatogonia, but then subject to MSCI in spermatocytes due to its X-linkage (Hasegawa, et al 2015), consistent with a previous report using RNA FISH (fluorescence in situ hybridization) analysis (Mueller, et al 2008). SCML2 protein is detected in the entire nuclei of undifferentiated spermatogonia and persists until meiosis, where it becomes accumulated on the XY body despite its transcriptional silencing (Hasegawa, et al 2015, Luo, et al 2015).…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Gensupporting
confidence: 91%
See 2 more Smart Citations
“…Another proteomics study independently identified SCML2 as a meiosis-specific protein (Luo, et al 2013). Scml2 is highly transcribed in spermatogonia, but then subject to MSCI in spermatocytes due to its X-linkage (Hasegawa, et al 2015), consistent with a previous report using RNA FISH (fluorescence in situ hybridization) analysis (Mueller, et al 2008). SCML2 protein is detected in the entire nuclei of undifferentiated spermatogonia and persists until meiosis, where it becomes accumulated on the XY body despite its transcriptional silencing (Hasegawa, et al 2015, Luo, et al 2015).…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Gensupporting
confidence: 91%
“…Scml2 is highly transcribed in spermatogonia, but then subject to MSCI in spermatocytes due to its X-linkage (Hasegawa, et al 2015), consistent with a previous report using RNA FISH (fluorescence in situ hybridization) analysis (Mueller, et al 2008). SCML2 protein is detected in the entire nuclei of undifferentiated spermatogonia and persists until meiosis, where it becomes accumulated on the XY body despite its transcriptional silencing (Hasegawa, et al 2015, Luo, et al 2015). Scml2 knockout mice are infertile (Hasegawa, et al 2015), while an independent Scml2 knockout mouse line with a distinct genetic background exhibits severely compromised fertility (Luo, et al 2015).…”
Section: Functions Of Single-copy Genes Vs Ampliconic/multi-copy Gensupporting
confidence: 91%
See 1 more Smart Citation
“…SCML2 is specifically expressed in germ cells of mice, and loss of SCML2 reduces sperm production. SCML2 also regulates the epigenetic state of sex chromosomes during male meiosis (24)(25)(26). Human SCML2 gene encodes two protein isoforms: SCML2A (chromatin-bound) and SCML2B (nucleoplasmic).…”
Section: Discussionmentioning
confidence: 99%
“…Sex comb on midleglike 2 (SCML2) is a germline-specific subunit of PRC1, and it can promote RNF2-dependent ubiquitination of H2A to mark somatic/progenitor genes on autosomes for repression. SCML2 can also recruit USP7, a deubiquitinase, to the XY body in spermatocytes, thereby preventing RNF2-dependent ubiquitination of H2A on sex chromosomes during meiosis and enabling unique epigenetic programming of sex chromosomes for male reproduction (Nakagawa et al 2008, Hasegawa et al 2015, Luo et al 2015. UBR2, an N-end rule proteolytic pathway ubiquitin ligase, can also catalyze H2A ubiquitination by promoting the HR6B (E2)-H2A interaction and the HR6B-to-H2A transfer of ubiquitin.…”
Section: Figurementioning
confidence: 99%